Identifying Hidden Li–Si–O Phases for Lithium‐Ion Batteries via First‐Principle Thermodynamic Calculations. Issue 3 (22nd April 2022) - Qu, Jiale; Ning, Chao; Feng, Xiang; Yao, Bonan; Liu, Bo; Lu, Ziheng; Wang, Tianshuai; Seh, Zhi Wei; Shi, Siqi; Zhang, Qianfan
Abstract : SiO–based materials are promising alloys and conversion‐type anode materials for lithium‐ion batteries and are recently found to be excellent dendrite‐proof layers for lithium‐metal batteries. However, only a small fraction of the Li–Si–O compositional space has been reported, significantly impeding the understanding of the phase transition mechanisms and the rational design of these materials both as anodes and as protection layers for lithium‐metal anodes. Herein, we identify three new thermodynamically stable phases within the Li–Si–O ternary system (Li2 SiO5, Li4 SiO6, and Li4 SiO8 ) in addition to the existing records via first‐principle calculations. The electronic structure simulation shows that Li2 SiO5 and Li4 SiO8 phases are metallic in nature, ensuring high electronic conductivity required as electrodes. Moduli calculations demonstrate that the mechanical strength of Li–Si–O phases is much higher than that of lithium metal. The diffusion barriers of interstitial Li range from 0.1 to 0.6 eV and the interstitial Li hopping serves as the dominating diffusion mechanism in the Li–Si–O ternary systems compared with vacancy diffusion. These findings provide a new strategy for future discovery of improved alloying anodes for lithium‐ion batteries and offer important insight towards the understanding of the phase transformation mechanism of alloy‐type protection layers on lithium‐metal anodes. Abstract : Applying high‐throughput crystal structure prediction to predict the Li–Si–O ternary system. Three new stable phases which have the potential to be applied as alloy anodes for lithium‐ion batteries were theoretically identified. The discovery of new predicted phases complements the electrochemical properties of the entire Li–Si–O system, demonstrating that the Li–Si–O ternary system has a broad prospect as a battery material.